Negative body image and avoidant retrieval of body-related autobiographical memories. Issue 2 (7th February 2023) - von Spreckelsen, Paula; Wessel, Ineke; Glashouwer, Klaske A.; de Jong, Peter J.
ABSTRACT: People with a negative body image may be more likely to recall negative memories of their body, but also be motivated to avoid retrieving specific memories to prevent triggering aversive emotions (e.g., disgust). Such inclination to retain at a global level of memory recall may hamper the correction of their negative body image. In previous research using Autobiographical Memory Tests (AMTs) with minimal instructions, we failed to find an overgeneral memory bias specific to individuals with a negative body image but observed low specificity overall in response to body cue words. In the present study ( N = 153), we included the traditional AMT next to a minimal instructions AMT and explored the idea that sensory reliving may be relevant to avoidance by assessing sensory reliving ratings next to memory specificity. A negative body image was associated with more negative body memories. In both AMTs, the findings failed to support our prediction that a more negative body image would be associated with lower specificity or sensory reliving. The findings are consistent with the view that autobiographical memories might be an important factor in defining one's body image, yet cast doubt on the relevance of avoidant retrieval of body-related memories in non-clinical samples.